Beighton scoring of joint laxity and injury incidence in Middle Eastern male youth athletes: a cohort study - Rejeb, Abdallah (BMJ Open Sport Exerc Med, 2019)
OBJECTIVES: To examine the association between generalised joint laxity (GJL) and injury rates in Middle Eastern male youth athletes. DESIGN: Prospective observational study consisting of GJL screen and injury audit (season 2009/2010). SETTING: Aspire Sports Academy Doha, Qatar. PARTICIPANTS: A total of 226 adolescent male athletes (mean age: 14.2 years; SD: 1.7; range: 10–18) involved in 15 sporting activities were grouped into contact and non-contact sports. All available athletes were included in this study. OUTCOME MEASURES: A seasonal injury audit, athletes’ anthropometric characteristics, for example, weight, height and body mass index and screen for GJL to determine Beighton Score (BS). RESULTS: The 226 athletes sustained 596 injuries and 75% reported at least one injury over a seasonal injury audit. Players in contact sports were injured more often than players in non-contact sports (more frequent injuries than injury-free time in contact sports; 127 days (95% CI 93 to 160) vs 176 days in non-contact sports (95% CI 118 to 234) (p<0.001). Survival analysis showed that gradient BS was not associated with injury HR=1.004 (95% CI 0.95 to 1.06) in the overall cohort. However, BS was associated with a greater injury risk in contact sports (HR: 1.29; 95% CI 1.05 to 1.59; p=0.015). CONCLUSION: Greater GJL, defined by gradient BS, plus involvement in contact sports together influence injury risk in youth athletes. Preseason documentation of GJL scoring should be considered specifically for contact sports as injury pre-emptive measure.